Virtualni model školskog atrija - Boj, Nataša (Array, 2020)
In the current globalization era, contemporary education has to take project-focused approach to teaching. Project was held in III OŠ ČK where visual model of the central school hall was designed, by implementing knowledge of subjects of Mathematics, Informatics and Technical Studies. Prior to the projects' start, survey has been held among students (N=108, M=52%, F=48%) to gain insights into what their opinion is on practically oriented teaching in the School. Sample included the students of 5th, 6th, 7th and 8th grade. The survey results showed that students think project assignments are being done overall more within elective courses. While working on this particular project, students were able to apply knowledge of Mathematics, Informatics, as well as Technical studies. Specifically, students examined school hall's surfaces (grass / wood / stone). Students made calculations of hall surfaces for the purpose of making price list. Price list included costs of each material used, and was gathered though googling on Internet. Further, students using ICT assembled the virtual model of the school hall. By use of 3D modelling, students made elements of the school hall - Pitagora's tree and a hexagonal prism. Other elements such as flowers have been added as photos downloaded from the internet. Subsequently, presentation following each project phase has been done. Further research is needed to gain deeper insights into practice-oriented assignments among students between grades 5 and 8. Recommendation is also to include projects/practical assignments as a compulsory part of curriculum.